Claire's cursed camping trip - Brandes, Wendy L 1965-; Lorenzet, Eleonora (North Mankato, Minnesota Stone Arch books, a Capstone imprint, 2017)
Twelve-year-old Claire is at summer camp with her friends, just as they have been doing for the past four years, but when Emily and Nina get into a fight, Claire finds herself in the middle and mad at both of them--right before the raft trip and forest hike that will require all their cooperation
English stories
RL: 4-6
1 2 13 15
NEW_ZTN_GN
Keywords: Best friends -- Juvenile fiction; Camping -- Juvenile fiction; Camps -- Juvenile fiction; Friendship -- Juvenile fiction; Hiking -- Juvenile fiction; Best friends -- Fiction; Camping -- Fiction; Camps -- Fiction; Friendship -- Fiction; Hiking -- Fiction